Implementation Of The Principal's Supervision On Teacher Performance - Sri Mures Walef; Nikmatulaili Nikmatulaili; Sufyarma Marsidin; Rifma Rifma (Jurnal Pendidikan Indonesia, 2023)
The purpose of this study was to determine teacher performance, implementation of school principal supervision, whether or not there was a relationship between the implementation of school principal supervision at SMKN 2 Kec. Guguak. This type of correlation research with the description method. The population of this study were teachers at SMKN 2 Kec. Guguak Which amounted to 65 people. This research is a population study because the population does not reach 100 people. The research instrument uses a questionnaire using a validated Likert scale. The results of the analysis show (1) implementing the supervision of the principal of SMKN 2 Kec. Guguak is quite implemented, (2) the teacher performance of SMKN 2 Guguak is quite implemented, (3) there is a significant relationship between the implementation of the supervision of school principals and teacher performance with an rcount distribution of 0.841 and r table of 0.317 at a 99% confidence level. In conclusion, the implementation of school principal supervision is one of the factors that influence the performance of teachers at SMKN 2 Kec. Guguak.